2016
DOI: 10.1016/j.aju.2016.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Innovative trends and perspectives for erectile dysfunction treatment: A systematic review

Abstract: ObjectiveTo review contemporary knowledge concerning the innovative trends and perspectives in the treatment of erectile dysfunction (ED).MethodsMedline was reviewed for English-language journal articles between January 2000 and March 2016, using the terms ‘erectile dysfunction treatments’, ‘new trends’ and ‘perspectives’. In all, 114 original articles and 16 review articles were found to be relevant. Of the 76 cited papers that met the inclusion criteria, 51 papers had level of evidence of 1a–2b, whilst 25 ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 74 publications
0
25
0
1
Order By: Relevance
“…Phosphodiesterase type-5 inhibitors (PDE5i), such as sildenafil, vardenafil, tadalafil, and avanafil, are currently the first-line therapy for ED. [ 10 , 11 ] These drugs enhance blood flow to the penis through nitric oxide (NO)/cyclic guanosine monophosphate signaling pathways. However, PDE5i agents are effective in only ∼60% of patients and are associated with adverse effects such as headache, flushing, and dyspepsia.…”
Section: Introductionmentioning
confidence: 99%
“…Phosphodiesterase type-5 inhibitors (PDE5i), such as sildenafil, vardenafil, tadalafil, and avanafil, are currently the first-line therapy for ED. [ 10 , 11 ] These drugs enhance blood flow to the penis through nitric oxide (NO)/cyclic guanosine monophosphate signaling pathways. However, PDE5i agents are effective in only ∼60% of patients and are associated with adverse effects such as headache, flushing, and dyspepsia.…”
Section: Introductionmentioning
confidence: 99%
“…ED is the process whereby sexually active men are unable to sustain an erection required for good sexual performance. Presently, about 150 million men has been estimated to be affected by this sexual dysfunction worldwide and it has also been reported that about 322 million men will be affected globally with ED in the next six years from now with about 2.5 times increase in Asia, Africa, and South America (Aytac, McKinlay, & Krane, ; Ismail & El‐Sakka, ).…”
Section: Introductionmentioning
confidence: 99%
“…will be affected globally with ED in the next six years from now with about 2.5 times increase in Asia, Africa, and South America (Aytac, McKinlay, & Krane, 1999;Ismail & El-Sakka, 2016).…”
mentioning
confidence: 99%
“…Erectile dysfunction (ED) is a common form of sexual dysfunction that is rampant among sexually active men, and it is estimated to affect about 322 million men globally by the year 2025 (Ismail and El-Sakka 2016). Kandeel et al (2001) reported that ED is a vascular disorder that is characterized by difficulty and/ or inability to attain/maintain penile erection for vaginal penetration.…”
Section: Introductionmentioning
confidence: 99%